Analisis Kemampuan Pemecahan Masalah Matematika Mahasiswa Berdasarkan Gender - Febrilia, Baiq Rika Ayu; Sanjaya, Pije; Setyawati, Dwi Utami; Juliangkary, Eliska (Media Pendidikan Matematika, 2023)
This study aims to analyze students' math problem-solving skills based on gender. The subjects involved were 6 students of the Mathematics Education Department, where three of them were female and the rest were male. The instrument used is a description question on the topic of Three Variable Linear Equation System that adapted through PISA standard questions. The analytical tool used is the problem-solving stage introduced by Polya. The results showed that at the stage of understanding the problem, male students were more able to understand the questions and some of them were able to rewrite them based on their own words. At the stage of making a solution plan, all male subjects could make a mathematical model of the given problem as well as for two female subjects, while there was one female subject who was unable to make a mathematical model. At the stage of carrying out the plan, the three male subjects were again able to complete the plan properly, while the female subject still had difficulty solving the problems given. At the review stage, all male subjects had re-examined, while all female subjects did not reach this stage. In general, male subjects have better problem solving abilities than female subjects.